Making it against the odds: How individual and parental co-agency predict educational mobility. (June 2021) - Schoon, Ingrid; Burger, Kaspar; Cook, Rose
Abstract: Introduction: This study examines the role of individual agency and parental co-agency as resource factors enabling educational mobility (university enrolment and degree completion) among first-generation students. Methods: The study is based on Next Steps, a nationally representative cohort of UK students. Path models were run, linking different dimensions of agency assessed at age 13/14 to educational attainment by age 25/26, controlling for academic attainment and socio-demographic factors. Results: Educational mobility was predicted by student's expectation to go to university, their expectation of success, and school engagement during secondary school. In addition, parental co-agency played a significant role - highlighting the importance of parents in supporting upward educational mobility of their children. Conclusions: Multiple dimensions of agency are necessary for disadvantaged students to achieve academically. To support first-generation students, schools need to provide opportunities for them to become engaged in education, to experience mastery and to develop realistic expectations of success.